Clinical and serological one-year follow-up of patients after the bite of Ixodes ricinus ticks infected with Borrelia burgdorferi sensu lato. Issue 4 (3rd April 2017) - Briciu, Violeta T.; Flonta, Mirela; Ţăţulescu, Doina F.; Meyer, Fabian; Sebah, Daniela; Cârstina, Dumitru; Mihalca, Andrei D.; Gherman, Călin M.; Hizo-Teufel, Cecilia; Huber, Ingrid; Fingerle, Volker; Lupșe, Mihaela
Abstract: Background: The risk of developing Lyme borreliosis (LB) after the bite of a Borrelia (B.) burgdorferi sensu lato (s.l.) infected tick in Romania is unknown. Methods: The present prospective study, performed in 2010–2011 in a hospital in Romania, has followed-up clinical and serological outcome of patients that presented with B. burgdorferi positive Ixodes (I.) ricinus bite. A second group of patients, including age, sex and residence-matched individuals bitten by B. burgdorferi negative ticks, was followed-up as a control group. The subjects' outcome was evaluated one year after the tick bite. Results: Forty-three out of 389 ticks detached from patients were positive by hbb Real-Time PCR (RT-PCR) for B. burgdorferi s.l. (mainly B. afzelii, but also B. garinii, B. burgdorferi sensu stricto, B. spielmanii/B. valaisiana and B. lusitaniae ). Twenty patients bitten by B. burgdorferi positive ticks and twenty matched control patients returned for the one year follow-up. Two patients from the B. burgdorferi positive group developed clinical manifestations of acute LB (erythema migrans) and 5 patients seroconverted (two from the B. burgdorferi positive group and three from the B. burgdorferi negative group). Borrelia afzelii was identified in ticks collected from persons that developed erythema migrans (EM). Comparing the two groups of patients, no statistical significant differences were found regarding presence of clinical symptoms or seroconversion. Conclusions: No outcome differences were found between the group of patients bitten by B. burgdorferi positive ticks and the group of patients bitten by B. burgdorferi negative ticks.